Transaction Costs and Governance Structures in the Public Sector - Peres, Ursula Dias (Review of Business Management, 2007)
The present paper presents an approach of the transaction costs theory applied in the public sector. In a first moment, some basic concepts used by the New Institutional Economy are presented, namely, transaction cost and governance structure. The second part of the paper focuses on the adaptation of this theory to the public sector, with special emphasis in the analysis of its actors, their transaction costs and other relevant peculiarities that affect the definition of the governance structure. As a way to equate part of the transaction costs present in the public sector, particularly the presence of political opportunism, the third part describes two possibilities of improving public management. Finally, in the conclusions, the paper emphasizes the need of establishing external incentive mechanisms and supervision towards a good public management, besides enhancing the studies on the efficiency and efficacy of the instruments described in the third part.Key-words:Transaction Costs. Governance Structure. Public Management. Governance in the Public Sector.